2023
DOI: 10.3390/met13030615
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics for Gallium-Based Liquid Alloys of Low Melting Temperature

Abstract: Gallium alloys are ideal base carriers for temperature-sensitive ferrofluids, which can be used for energy convection, soft robotics, microchannels, magnetorheological devices, etc. In this study, gallium was mixed with different substances (In, Sn, Zn, Ge, and Al) to obtain a low melting point, reduce the wetness and adhesion of its alloys, and realize low viscosity. The melting point, contact angle on certain solid plates, viscosity, and viscoelasticity of the gallium alloys were measured, and some useful ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…All the previous works have also reported that storage modulus dominates the viscous modulus of LM similarly in air. Researchers have investigated the modulus using different rheometers based on different working principles but still have reported a similar difference between the modulus [ 12 , 14 , 27 , 62 ]. As the volume is constantly oscillating in a short range [cf figures 7 (b)–(d)], the oxide layer is continuously evolving (either rupturing or stretching into new oxides) [ 24 , 92 ] as the yielded surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the previous works have also reported that storage modulus dominates the viscous modulus of LM similarly in air. Researchers have investigated the modulus using different rheometers based on different working principles but still have reported a similar difference between the modulus [ 12 , 14 , 27 , 62 ]. As the volume is constantly oscillating in a short range [cf figures 7 (b)–(d)], the oxide layer is continuously evolving (either rupturing or stretching into new oxides) [ 24 , 92 ] as the yielded surface.…”
Section: Resultsmentioning
confidence: 99%
“…However, we can further leverage the techniques to investigate the kinetic behavior of the LM oxide layer. We first validated our dilatational results with previous literature to compare the elastic and viscous components of the LM [ 12 , 14 , 27 , 62 ]. As proof of concept, we also present the LM droplet turning into a softer material by showing the gradual elastic modulus reduction.…”
Section: Introductionmentioning
confidence: 93%
“…8 The melting point of LMs can be adjusted below room temperature by varying their composition. 9 GLMs can flow and deform freely at room temperature. Based on the analysis of chemical microstructures, it can be known that the force between Ga and Ga or between Ga and other metal atoms is not as strong as that for solid metal.…”
Section: Introductionmentioning
confidence: 99%
“…Given the issues above, liquid metal (LM) is considered a good alternative with enormous potential for flexible electronics due to its especially high electrical conductivity comparable to rigid metal , while possessing unique liquid-like deformability. , Despite high processability, virgin LM has a high surface tension, making it difficult to be well dispersed and patterned onto the substrate directly . Although the encapsulation of liquid metal nanoparticles (LMNPs) through an organic shell layer could improve their stable dispersion, the conductivity would be impaired, making the extra sintering of the ink necessary. , …”
Section: Introductionmentioning
confidence: 99%